The introduction of a standardised national licensing exam as a driver of change in medical education: A qualitative study from Switzerland. (2nd October 2020) - Huwendiek, Sören; Jung, Daniel; Schirlo, Christian; Huber, Philippe; Balestra, Gianmarco; Guttormsen, Sissel; Berendonk, Christoph
Abstract: Introduction: Only a few studies have described the impacts, strengths and needs for further development of national licensing exams (NLE). To gain such insights regarding the Swiss NLE, which includes a multiple-choice and a standardised clinical skills exam, we explored the perceptions of involved experts and stakeholders. Methods: We explored participants' perceptions in four focus group discussions. The interviews were recorded, transcribed verbatim and qualitatively analysed using a thematic analysis approach. Results: The analysis resulted in five perceived impacts, two strengths and two needs for further developments of the NLE. Perceived impacts were (1) steering students' learning behaviour, (2) supporting teachers and assessors to align teaching to competencies, (3) elevating the importance of the Swiss Catalogue of Learning Objectives, (4) setting incentives for the further development of curricula, and (5) fostering the collaboration between the faculties of medicine. Perceived strengths were the blend of assessment formats, including their competency-based orientation, and the collaborative development approach. Perceived needs lay in the NLE's further development to sustain its fit for purpose and in incentives for people involved. Conclusion: According to our study, this NLE had, and has, notable impacts on medical education in Switzerland. Our insights can be useful for others planning a similar undertaking.